The Effect of Supply chain planning and operations on Employee Performance through Employee Job Satisfaction - Setyo Widodo, Djoko; Sanusi Silitonga, P. Eddy (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to determine the effect of the work environment and supply chain planning and operationson, work environment and leadership on job satisfaction and its implication toward the performance of the job satisfaction,Â  job satisfaction on performance and work environment and leadership through job satisfaction on performance. The sample size in this study using Slovin formula with large ? used is 5%, thus the sample size is 80 people. Research used a quantitative analysis method, using path analysis, followed by determination analysis (R Square), partial hypothesis testing (t-test) and simultaneous (F test) with alpha 5 percent (0.05). The analytical tool uses SPSS version 21.0 for windows. The results of this study show that leadership and work environment have a positive and significant effect on employee performance and satisfaction as well as job satisfaction, have an influence on the performance of employees.